2015
DOI: 10.1002/elps.201400326
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoresis of spermatozoa in viscoelastic medium

Abstract: Knowledge of spermatozoa motility is important in selecting suitable spermatozoa for assisted reproduction procedures. By considering the internal sliding force within an active filament, its shape in a viscoelastic Oldroyd-B fluid subjected to nonuniform electric field is presented. The resulting velocity is a function of the beating pattern and DEP force, which is dependent on the spermatozoon's morphology as well as the gradient of the mean square electric field. Finally, the velocities of the X- and Y-sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…We also consider the use of machine learning in investigating the sorting of sperm by dielectrophoresis, where the force is modelled as F DEP = C 0 Γi [57,58] and where Γ is the shape factor [59] rather than volume. The conclusions drawn are similar to those above-consistent predictions with little variance are obtained when a training size of 10,000 is used-but the results are always a couple of percentage points higher than results obtained from the full computation for 10 5 samples.…”
Section: Resultsmentioning
confidence: 99%
“…We also consider the use of machine learning in investigating the sorting of sperm by dielectrophoresis, where the force is modelled as F DEP = C 0 Γi [57,58] and where Γ is the shape factor [59] rather than volume. The conclusions drawn are similar to those above-consistent predictions with little variance are obtained when a training size of 10,000 is used-but the results are always a couple of percentage points higher than results obtained from the full computation for 10 5 samples.…”
Section: Resultsmentioning
confidence: 99%
“…Artificial swimmers have thereafter been used to demonstrate experimentally that reciprocal motion is possible in a polymeric fluid (Keim et al 2012). Therefore, models ought to incorporate the nonlinearity of fluid behavior if the object of study resides in a non-Newtonian environment (Koh and Marcos 2015a). In this section, we shall explore the extent to which the kinematic behavior of swimmers vary under different fluid medium, and determine if the various studies provide a common relation which may then be used as a correcting factor.…”
Section: Stress-strain Relation Of Fluidmentioning
confidence: 98%
“…The DEP force and Clausius–Mossotti (CM) factor are defined, respectively, in the following equations: bold-italicFDEP=2πrp3normalε0εKE2, K=εpεεp+2ε,where r p is the particle radius, E is the electric field, ε 0 is the permittivity of the free space, and ε and ɛ p are fluid and particle permittivity, respectively. To date, a few works considered DEP through VEFs (Koh, ). For the first time, Lu, DuBose, Joo, Qian, and Xuan () and Lu et al () used a DEP method for particle manipulation utilizing viscoelastic PEO solution.…”
Section: Active Particle Manipulation In Vefsmentioning
confidence: 99%
“…Lu et al () concluded that the constriction‐induced DEP is not an appropriate method for focusing of particles in VEFs. However, the modeling results of Koh and Marcos (Koh, ) predicted that in suitable electric field strength, the DEP force could separate spermatozoa containing the desired chromosome in a VEF flow with low concentration. Furthermore, Zhou et al () developed a numerical model to study DEP‐based particle manipulation in VEFs through a converging‐diverging microchannel.…”
Section: Active Particle Manipulation In Vefsmentioning
confidence: 99%
See 1 more Smart Citation